Heat storage material and heat storage film
Patent Information
- Application Number
- JP2023134695
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-22
AI Technical Summary
【0010】 本発明の蓄熱材及び蓄熱フィルムによれば、固体状態を維持したままで蓄熱及び放熱が可能であるため、取扱い性が非常に高い。1つの実施形態において、この蓄熱材及び蓄熱フィルムによれば、実用レベルの高い蓄熱性能及び放熱性能を容易に与えることができる。1つの実施形態において、この蓄熱材及び蓄熱フィルムによれば、フィルム化が容易で、かつ透明性を容易に与えることができる。従来技術の蓄熱材料は、相転移前後の両状態で透明とはならないが、本発明の1つの実施形態の蓄熱材料によれば、結晶性側鎖の結晶が融解する前後において、透明性を維持することができるため、窓ガラス、食品包装フィルム等の透明性が求められる用途において、非常に有利である。
Smart Images

Figure 2025029833000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat storage material and a heat storage film. [Background technology]
[0002] In recent years, from the viewpoint of reducing carbon dioxide emissions, etc., active research and development has been conducted on how to effectively utilize thermal energy in building materials such as wall materials, floor materials, ceiling materials, roof materials, etc. Latent heat storage materials are known as one of the materials for this purpose.
[0003] Latent heat storage materials are materials that can store thermal energy by utilizing the phase change of a material, such as from solid to liquid. Unlike insulating materials, latent heat storage materials can efficiently use heat because the stored heat and cold can be used as thermal energy when needed. In particular, the phase change from solid to liquid is relatively easy to handle and can store a large amount of heat, so a variety of materials are known in organic substances such as block copolymers and paraffin, and inorganic substances such as sodium sulfate salts.
[0004] For example, Non-Patent Document 1 discloses that the thermal efficiency of buildings is improved when double-glazing is used in which paraffin, a latent heat storage material, is filled between the panes of glass.
[0005] In addition, Non-Patent Document 2 reports that a polyalkylacrylamide comb polymer has crystallinity in the alkyl side chain portion, and that the temperature at which the alkyl side chain crystals melt (melting point) is lower than the glass transition temperature of the comb polymer. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Changyu Liu, et al., “Effect of PCM thickness and melting temperature on thermal performance of double glazing units”, Journal of Building Engineering, 11(2017), 87-95 [Non-Patent Document 2] Kazuki Ebata, et al., “Nanophase Separation of Poly( N- alkyl acrylamides): The Dependence of the Formation of Lamellar Structures on Their Alkyl Side Chains”, Macromolecules, 2019, 52, 9773-9780 Summary of the Invention [Problem to be solved by the invention]
[0007] Conventional heat storage materials use phase changes in all processes of heat storage and heat release, so they are assumed to become liquid either before or after the process. In addition, conventional heat storage materials are all cloudy because they are used in a powder solid state. Furthermore, heat storage materials that use paraffin need to be encapsulated, so they are difficult to make into a film. Heat storage materials that use block copolymers use latent heat associated with the melting of polymers, so even if they can be made into a film, there is an issue that the mechanical properties change significantly during the heat storage and heat release processes.
[0008] An object of the present invention is to provide a novel heat storage material and heat storage film that are capable of storing and releasing heat while maintaining a solid state. [Means for solving the problem]
[0009] The present inventors have found that the above problems can be solved by the following aspects. Aspect 1 A heat storage material comprising a comb polymer having an amorphous backbone and crystalline side chains, the comb polymer having a glass transition temperature greater than the melting point of the crystalline side chains. Aspect 2 2. The thermal storage material of claim 1, wherein the comb polymer has the amorphous main chain, the crystalline side chain, and a linking group that links the amorphous main chain and the crystalline side chain, the linking group including a polar group. Aspect 3 The thermal storage material according to aspect 2, wherein the linking group includes one or more groups selected from the group consisting of an amide group, a urea group, a urethane group, a thioamide group, a thiourea group, and a thiourethane group. Aspect 4 The crystalline side chain is C4 to C 30 2. The thermal storage material of embodiment 1, comprising a hydrocarbon-based group: Aspect 5 2. The heat storage material according to aspect 1, wherein the amorphous main chain is a hydrocarbon-based main chain having a degree of polymerization of 5 to 1,000. Aspect 6 The heat storage material according to aspect 1, wherein the comb polymer has a nano-phase-separated structure having nano-domains due to crystals of the crystalline side chains. Aspect 7 The amorphous main chain is a hydrocarbon main chain having a degree of polymerization of 5 to 1000, and the crystalline side chain is a straight or branched C 12 ~C 18 and the linking group comprises one or more groups selected from the group consisting of an amide group, a urea group, and a urethane group. Aspect 8 A heat storage film comprising the heat storage material according to any one of the first to seventh aspects. Aspect 9: The heat storage film according to embodiment 8, wherein the heat storage film has an average absorbance of 0.5 or less in an absorption spectrum at wavelengths of 400 to 800 nm when formed on a glass substrate to a thickness of 100 μm. Aspect 10 A laminated heat storage film comprising the heat storage film according to embodiment 8 and another polymer film. Effect of the Invention
[0010] According to the heat storage material and heat storage film of the present invention, heat storage and heat release are possible while maintaining the solid state, and therefore the handling is very easy. In one embodiment, according to this heat storage material and heat storage film, it is possible to easily provide a heat storage performance and heat release performance at a practical level. In one embodiment, according to this heat storage material and heat storage film, it is easy to form a film and to easily provide transparency. Although the heat storage material of the prior art is not transparent both before and after the phase transition, according to the heat storage material of one embodiment of the present invention, it is possible to maintain transparency before and after the crystals of the crystalline side chain melt, and therefore it is very advantageous in applications requiring transparency such as window glass and food packaging film. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows the appearance of the heat storage laminated film produced in the example. [Diagram 2] FIG. 2 shows the results of differential scanning calorimetry of polyoctadecylacrylamide. [Diagram 3] FIG. 3 is a graph of the light absorption spectrum of the heat storage film, showing the transparency of the heat storage film. [Figure 4] FIG. 4 is a graph of the light absorption spectrum of the heat storage laminate film, showing the transparency of the heat storage film. [Diagram 5] FIG. 5 shows the results of a temperature increase and decrease test of the heat storage film. [Figure 6] FIG. 6 shows the results of a temperature increase and decrease test of the heat storage laminate film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In one embodiment, the thermal storage material of the present invention comprises a comb polymer having an amorphous backbone and crystallizable side chains, the glass transition temperature of the comb polymer being greater than the melting point of the crystallizable side chains.
[0013] In another embodiment, the method of use of the present invention is a method of using a comb polymer having an amorphous main chain and crystalline side chains in a heat storage material, wherein the glass transition temperature of the comb polymer is higher than the melting point of the crystalline side chains.
[0014] Here, the "glass transition temperature" and the "melting point" are determined from the DSC curve measured when the comb polymer is measured by a differential scanning calorimeter (DSC). For example, at the "glass transition temperature", a shift in the baseline of the endothermic heat occurs, and at the "melting point", a peak appears in the endothermic heat. Here, a part of the main chain of the comb polymer may be crystalline, and a part of the side chain may also be amorphous, but the "glass transition temperature" is due to the amorphous main chain, and the "melting point" is due to the crystalline side chain. In addition, amorphousness and crystallinity refer to the state at the temperature at which this heat storage material is used, and when it is used near room temperature, the amorphous main chain and the crystalline side chain may be amorphous and crystalline at room temperature, respectively.
[0015] Usually, when a polymer having an amorphous part and a crystalline part is heated from low temperature to high temperature, the glass transition temperature is reached first and the motion of the amorphous part starts. When the temperature is further increased, crystallization occurs, and then the melting point is reached and the crystalline part of the crystalline part melts. In contrast, the present inventors have found that in the case of some comb polymers having an amorphous main chain and a crystalline side chain, the crystalline part of the crystalline side chain melts first and the motion of that part starts, and then the motion of the amorphous main chain starts. In this case, the glass transition temperature, which is usually lower than the melting point, is observed at a temperature higher than the melting point of the crystalline side chain.
[0016] The present inventors have found that such comb polymers are extremely useful as heat storage materials. That is, latent heat storage materials can usually store thermal energy by utilizing a phase change between liquid and solid, but the comb polymer used in the present invention can cause crystalline melting and crystallization of the crystalline side chains while remaining in a solid state below the glass transition temperature, thereby absorbing and releasing heat, resulting in very high handleability. In addition, the comb polymer used in the present invention can easily provide high heat storage and heat release performance at a practical level. Furthermore, such comb polymers can be easily made into films and can easily be given transparency, making them very advantageous in applications requiring transparency, such as window glass and food packaging films, which are difficult to envision with heat storage materials of the prior art.
[0017] The glass transition temperature of the comb polymer may be, for example, 30° C. or more, 40° C. or more, 50° C. or more, or 60° C. or more, and 120° C. or less, 100° C. or less, 90° C. or less, or 80° C. or less. For example, the glass transition temperature of the comb polymer can be 30° C. or more and 120° C. or less, or 50° C. or more and 100° C. or less.
[0018] The melting point of the crystalline side chains of the comb polymer may be, for example, −30° C. or higher, −20° C. or higher, −10° C. or higher, 0° C. or higher, 10° C. or higher, or 20° C. or higher, or may be 50° C. or lower, 40° C. or lower, 20° C. or lower, 10° C. or lower, or 0° C. or lower. For example, the melting point of the comb polymer can be −30° C. or higher and 50° C. or lower, or 0° C. or higher and 40° C. or lower.
[0019] The glass transition temperature of the comb polymer may be, for example, 30° C. or more, 40° C. or more, 50° C. or more, or 60° C. or more, and may be 80° C. or less, 70° C. or less, 60° C. or less, or 50° C. or less, higher than the melting point of the crystallizable side chains. For example, the glass transition temperature of the comb polymer may be 30° C. or more and 80° C. or less, higher than the melting point of the crystallizable side chains.
[0020] The number average molecular weight (Mn) of the comb polymer may be, for example, 5000 or more, 10000 or more, 15000 or more, 20000 or more, or 30000 or more, or 200000 or less, 100000 or less, 80000 or less, 60000 or less, or 50000 or less. For example, the number average molecular weight (Mn) of the comb polymer may be 5000 or more and 200000 or less, or 20000 or more and 100000 or less. Here, the number average molecular weight (Mn) is determined in terms of standard polystyrene by gel permeation chromatography as described in the examples.
[0021] The molecular weight distribution (Mw / Mn) of the comb polymer may be, for example, 1.0 or more, 1.2 or more, 1.5 or more, 2.0 or more, or 2.5 or more, and 5.0 or less, 4.0 or less, or 3.0 or less. For example, the molecular weight distribution (Mw / Mn) of the comb polymer may be 1.0 or more and 5.0 or less, or 2.0 or more and 4.0 or less. The molecular weight distribution (Mw / Mn) is also determined in terms of standard polystyrene by gel permeation chromatography as described in the Examples.
[0022] The average degree of polymerization of the comb polymer may be 6 or more, 8 or more, 10 or more, 20 or more, or 50 or more, and may be 1000 or less, 500 or less, 300 or less, 100 or less, 50 or less, 30 or less, or 20 or less. This average degree of polymerization may be, for example, 6 or more and 1000 or less, or 8 or more and 300 or less. The average degree of polymerization can be determined by determining the molecular weight in terms of standard polystyrene by gel permeation chromatography described in the examples. By adjusting the molecular weight, degree of polymerization, etc. of the comb polymer, the use temperature range, transparency, etc. of the heat storage material can be changed.
[0023] In one embodiment, the heat storage material includes a comb polymer having an amorphous main chain, a crystalline side chain, and a linking group that links the amorphous main chain and the crystalline side chain, the linking group including a polar group. The comb polymer having such a linking group can reduce the degree of freedom of movement of the amorphous main chain by the intermolecular interaction of the linking group with the surrounding chemical groups, and can melt the crystals of the crystalline side chain before the amorphous main chain starts to move. Therefore, such a heat storage material can store and release heat while maintaining a solid state.
[0024] The polar group is not limited as long as it can reduce the degree of freedom of movement of the amorphous main chain by intermolecular interaction with surrounding chemical groups, and may contain, for example, oxygen, nitrogen, sulfur, phosphorus, halogen, etc. For example, the linking group may be a group formed by at least one of an ester group, a thioester group, an ether group, a thioether group, a carbonyl group, an amide group, an amine oxide group, an amino group, and a polyoxyalkylene group.
[0025] The linking group may particularly include a secondary amino group, and may include an ether group, an ester group, a thioether group, and / or a thioester group in addition to the secondary amino group. In this case, the linking group may exert a strong intermolecular interaction, such as a hydrogen bond, which tends to reduce the degree of freedom of movement of the amorphous main chain.
[0026] Specifically, the linking group may include one or more groups selected from the group consisting of an amide group (-CO-NH-), a urea group (-NH-CO-NH-), a urethane group (-NH-CO-O-), a thioamide group (-CS-NH-), a thiourea group (-NH-CS-NH-), and a thiourethane group (-NH-CS-O-, -NH-CO-S-, or -NH-CS-S-).
[0027] The main chain of the comb polymer is amorphous, but a part of it may be crystalline as long as the advantageous effects of the present invention are achieved. The main chain of the comb polymer can form a structure called a nanophase separation structure together with nanodomains formed by crystals constituted by the crystalline side chains, and the entire comb polymer can be in an amorphous glass state.
[0028] The repeating unit of the amorphous main chain of the comb polymer is not particularly limited as long as the advantageous effects of the present invention can be obtained, and may be, for example, a hydrocarbon group. In this specification, the hydrocarbon group refers to a hydrocarbon group that may contain a heteroatom (e.g., oxygen, nitrogen, sulfur, phosphorus, halogen, etc.), may be branched, or may contain a cyclic group. For example, the amorphous main chain of the comb polymer may be obtained by polymerizing an unsaturated hydrocarbon group.
[0029] The side chains of the comb polymer are crystalline, but may be partially amorphous as long as they provide the advantageous effects of the present invention. The side chains of the comb polymer can form nano-sized aggregates and become nano-domains of a nanophase-separated structure. The aggregates can have an average major axis of, for example, 100 nm or less, 50 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, or 5 nm or less, which makes the comb polymer transparent to visible light. The size of the aggregates can be determined by X-ray diffraction, as described in Non-Patent Document 2.
[0030] The crystalline side chain of the comb polymer is not particularly limited as long as it provides the advantageous effects of the present invention, but may be, for example, a hydrocarbon group. For example, the hydrocarbon group may in particular be an alkyl group having a straight or branched chain.
[0031] The number of carbon atoms in the crystalline side chain may be, for example, 4 or more, 6 or more, 8 or more, 10 or more, 12 or more, or 15 or more, and may be 50 or less, 40 or less, 30 or less, 25 or less, 20 or less, or 18 or less. The number of carbon atoms may be, for example, 4 to 50 or 10 to 30. By adjusting the number of carbon atoms in the crystalline side chain, the temperature range of use of the heat storage material, etc., can be changed.
[0032] The method for producing the comb polymer is not particularly limited, but for example, the comb polymer can be obtained by reacting a first precursor compound containing a portion that will become a main chain and a part of a linking group with a second precursor compound containing a portion that will become a linking group and a side chain, and then polymerizing the portion that will become the main chain. Alternatively, the second precursor compound can be grafted after polymerizing the first precursor compound.
[0033] For example, when producing poly(meth)acrylamide having alkyl side chains, a (meth)acryloyl halide such as acryloyl chloride is reacted with an alkylamine to obtain an N-alkyl(meth)acrylamide, which is then radically polymerized in an organic solvent to produce a comb polymer. For example, the type and number of alkyl groups in the alkylamine can be adjusted to change the side chains of the comb polymer.
[0034] The comb polymer thus produced has one repeat unit having one side chain pendant to one monomer, but may be a copolymer having multiple types of repeat units in a block or random configuration by copolymerizing such a monomer with another monomer. The comb polymer preferably has at least 50 mol %, at least 70 mol %, at least 80 mol %, at least 90 mol %, at least 95 mol %, or at least 100 mol % of repeat units having a side chain.
[0035] The comb polymer can have high heat storage and release performance, and the amount of latent heat obtained can be, for example, 5 J / g or more, 10 J / g or more, 20 J / g or more, or 30 J / g or more, and may be 200 J / g or less, 100 J / g or less, 80 J / g or less, 50 J / g or less, or 30 J / g or less. The amount of latent heat obtained by the comb polymer can be, for example, 5 J / g or more and 200 J / g or less, or 30 J / g or more and 50 J / g or less.
[0036] As long as the advantageous effects of the present invention are not lost, the heat storage material may contain other substances in addition to the comb polymer depending on its application. For example, the heat storage material may be used by blending the comb polymer with other polymers, and examples of such polymers include polystyrene-based resins, polyester-based resins, acrylic-based resins, polyamide-based resins, polyvinyl alcohol-based resins, polyurethane-based resins, polyolefin-based resins, polycarbonate resins, polysulfone resins, and derivatives thereof, as well as mixtures thereof. The heat storage material may further contain optional additives such as fillers, lubricants, antistatic agents, release agents, plasticizers, antioxidants, antibacterial agents, antifungal agents, and ultraviolet absorbers, as necessary, depending on its application.
[0037] The thermal storage material may contain 10% or more, 10% or more, 30% or more, 50% or more, 70% or more, 90% or more, or 95% or more by weight of the comb polymer, or 100% or less, 95% or less, 90% or less, 80% or less, 60% or less, or 40% or less by weight of the comb polymer. For example, the thermal storage material may contain 10% or more and 100% or less by weight of the comb polymer.
[0038] In one embodiment, the present invention relates to a heat storage film containing the heat storage material as described above. When the heat storage material is used as a film, it is preferable because it can be used for various purposes by being attached to a window glass or used as a part of a packaging film.
[0039] In another embodiment, the method of use of the present invention is the use of a comb polymer as described above in a thermal storage film.
[0040] In one embodiment, the heat storage film can be transparent to visible light. Even if the heat storage material of the prior art is made into a film, it cannot be transparent throughout the entire process of heat storage and heat dissipation, whereas the heat storage film of the present invention can be transparent throughout the entire process of heat storage and heat dissipation. Here, transparency means that when a film is formed on a glass substrate with a thickness of 100 μm, the average absorbance of the absorption spectrum at a wavelength of 400 to 800 nm is 0.5 or less, particularly 0.3 or less, 0.1 or less, 0.05 or less, or 0.01 or less.
[0041] Such a heat storage film can be very suitably used in windows of buildings, front and rear glass of cars, food films for covering fresh food, vinyl greenhouses in plant production, and the like.
[0042] The thickness of the heat storage film is not particularly limited and may be, for example, 10 μm or more, 50 μm or more, 100 μm or more, 500 μm or more, 1 mm or more, or 5 mm or more, or 100 mm or less, 10 mm or less, 1 mm or less, 500 μm or less, 100 μm or less, or 50 μm or less.
[0043] As a method for forming the heat storage film, known methods such as a solution casting method (solution casting method), a melt extrusion method, a calendar method, and a compression molding method can be used. Among these, a solution casting method and a melt extrusion method can be mentioned. As an apparatus for carrying out the solution casting method, for example, a drum type casting machine, a band type casting machine, a spin coater, etc. can be mentioned. As a melt extrusion method, a T-die method, an inflation method, etc. can be mentioned. When a film is formed by the melt extrusion method, it may be made into a stretched film by stretching.
[0044] The heat storage film can be laminated with another polymer film to be used as a laminated heat storage film. By using another polymer film as a base film, the heat storage film can be used for various purposes.
[0045] Other polymer films include, for example, polyolefin films such as polyethylene and polypropylene, polyester films such as polyethylene terephthalate and polybutylene terephthalate, polyamide films such as 6-nylon and 6,6-nylon, polystyrene films, vinyl chloride films, and synthetic paper.
[0046] When a laminated heat storage film is obtained, the heat storage film and another polymer film can be laminated by a known method such as coextrusion, thermocompression bonding, extrusion lamination, or dry lamination.
[0047] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. EXAMPLES
[0048] Example of production Comb polymer N-Octadecylamine (3.60 g) was dissolved in chloroform (60 mL) and stirred at 0° C. To this solution was added triethylamine (2.00 mL) followed by dropwise addition of acryloyl chloride (1.17 mL). After addition of acryloyl chloride, the reaction mixture was stirred at 20° C. for 4 hours prior to the addition of methanol (5 mL). Most of the solvent was then evaporated under reduced pressure and THF (120 mL) was added. The resulting precipitate was filtered and the filtrate was evaporated under reduced pressure to precipitate a white solid of N-octadecylacrylamide (ODA).
[0049] This white solid was dissolved in methanol (300 mL) and stored in a refrigerator for 1 day to promote recrystallization of ODA. The resulting crystals were identified by proton NMR measurement. Next, ODA was dissolved in toluene, and 1 mol% of 2,2'-azobisisobutyronitrile (AIBN) was added as an initiator and reacted at 60 °C for 12 h to carry out free radical polymerization. The polymerization solvent was concentrated, and a comb-shaped polymer, polyoctadecylacrylamide (p(ODA)), was produced by reprecipitation using acetonitrile as a poor solvent.
[0050] The above reaction formula is shown below.
[0051] [ka]
[0052] <Heat storage film> A film was formed on a glass substrate by casting using pODA as the comb polymer. The film thickness measured by a stylus step gauge was 100 μm.
[0053] <Heat storage laminated film> A pODA film was produced by casting on a commercially available wrap (NEW Polywrap, Ube Films Co., Ltd.). For ease of handling, the commercially available wrap was laid on a glass substrate, and the pODA film was produced on top of it. When pODA was cast on the wrap, the wrap wrinkled as shown in Figure 1, but transparency was maintained. This is thought to be due to the shrinkage of pODA when the solvent dries.
[0054] Evaluation and Results <Glass transition temperature and melting point> The glass transition temperature and melting point of the comb polymer were measured using a differential scanning calorimeter (DSC; DSC 8231, Rigaku Corporation) at a nitrogen flow rate of 50 mL / min and a heating rate of 10° C. / min.
[0055] The results of DSC measurement of pODA are shown in FIG.
[0056] The DSC spectrum of pODA in Figure 2 has a large endothermic peak at 31.9°C and also shows a baseline shift at around 82.3°C. The former is a first-order phase transition, and is thought to result from the melting of alkyl chains that have aggregated due to nano-phase separation of polar main chains and hydrophobic alkyl chains. On the other hand, the latter is a second-order phase transition, and is the glass transition temperature. Since the difference between these temperatures is more than 50°C, it was found that the polyoctadecylacrylamide heat storage material exhibits latent heat storage function without significant changes in its mechanical properties.
[0057] <Molecular weight> The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of pODA were measured by gel permeation chromatography (GPC; Shodex GPC-101, Resonaq Co., Ltd.) using standard polystyrene. The columns used were TSKgel Super HZ2000, TSKgel Super HZ3000, TSKgel Super HZ4000, and TSKgel Super HZM-M, Tosoh Corporation, connected in this order.
[0058] As a result, the number average molecular weight of pODA was 40,000, and the molecular weight distribution (Mw / Mn) was 3.4.
[0059] Optical absorption spectrum The absorbance of light in the wavelength range of 300 nm to 800 nm was measured by ultraviolet-visible-near infrared spectroscopy (UV3600i Plus, Shimadzu Corporation) for a sample of only the glass substrate and a sample of the glass substrate on which the heat storage film was formed.
[0060] Similar measurements were also carried out on a sample in which only the commercially available wrap was laminated on the glass substrate, and on a sample in which the commercially available wrap was laminated on the glass substrate and coated with pODA.
[0061] The results are shown in FIG. 3 and FIG.
[0062] As shown in FIG. 3, the sample with only the glass substrate and the sample with the glass substrate on which the heat storage film is formed have substantially the same absorbance in the visible light range, indicating that the heat storage film is transparent.
[0063] Furthermore, as shown in Figure 4, when comparing a sample in which only plastic wrap was laminated on a glass substrate with a sample in which plastic wrap was laminated on a glass substrate and coated with pODA, the sample coated with the pODA film did not show any specific absorption peak, and only showed an increase in the background due to scattering caused by wrinkles in the plastic wrap.
[0064] <Temperature increase and decrease tests> The above-mentioned heat storage film formed on a glass substrate was attached with a fiber thermometer on the glass substrate, and left at 23°C for 20 seconds, then placed on a hot plate at 48°C with the glass substrate side down to measure the temperature change. The substrate was then removed from the hot plate and left at room temperature. Similarly, measurements were made on the glass alone.
[0065] Similar measurements were also carried out on a sample in which only plastic wrap was laminated on the glass substrate, and on a sample in which plastic wrap was laminated on the glass substrate and coated with a pODA film.
[0066] The temperature changes are shown in Figs. 5 and 6.
[0067] As shown in Figure 5, when measuring the glass substrate alone, a temperature rise was observed immediately after placing it on the hot plate (at 20 seconds), whereas for the glass substrate coated with pODA, the temperature rise was observed 2 seconds later and at a more gradual rate. In addition, the maximum temperature was 43.2°C for the glass substrate alone, whereas it was 42.2°C for the glass substrate coated with pODA, a drop of 1°C.
[0068] Furthermore, when the glass substrate was removed from the hot plate (at 80 seconds) and left at room temperature, the temperature of the glass substrate alone dropped quickly, whereas the temperature of the glass substrate coated with pODA dropped slowly. This is because when the substrate was placed on the hot plate, the alkyl side chains melted and absorbed the heat, preventing it from becoming too hot, whereas when the substrate was removed from the hot plate, the molten alkyl chains caused nanocrystallization, generating heat. The transparency of pODA did not change with this temperature change. This demonstrated that the pODA film exhibits latent heat storage functionality while maintaining its transparency.
[0069] As shown in Figure 6, similar to Figure 5, the sample in which the pODA film was coated on the wrap on the glass substrate had a longer delay in the temperature rise and the rise was also more gradual. Furthermore, the temperature reached was 0.5°C lower than that in the case of the wrap alone.
[0070] The transparency was also maintained in the sample where the pODA film was coated on plastic wrap. Thus, it was found that pODA can be easily applied not only to hard glass substrates but also to soft plastic wrap, and maintains its transparency and latent heat storage function. This is because the melting and crystallization of the crystalline side chains, which are the origin of latent heat storage, occurs below the glass transition temperature, so the glassy state of the film is maintained.
[0071] In addition, when a similar experiment was performed by changing the number of carbon atoms in the octadecyl group (alkyl group) of octadecylamine from 12 to 17 to obtain comb-shaped polymers with various side chain lengths, roughly the same results were obtained, although the appropriate temperature range, etc. changed depending on the melting point.
Claims
1. A heat storage material comprising a comb polymer having an amorphous backbone and crystalline side chains, the comb polymer having a glass transition temperature greater than the melting point of the crystalline side chains.
2. The heat storage material according to claim 1 , wherein the comb polymer has the amorphous main chain, the crystalline side chain, and a linking group that links the amorphous main chain and the crystalline side chain, and the linking group includes a polar group.
3. The heat storage material according to claim 2 , wherein the linking group comprises one or more groups selected from the group consisting of an amide group, a urea group, a urethane group, a thioamide group, a thiourea group, and a thiourethane group.
4. The crystallizable side chain is C 4 ~C 30 The heat storage material according to claim 1 , comprising a hydrocarbon group of the formula:
5. The heat storage material according to claim 1, wherein the amorphous main chain is a hydrocarbon-based main chain having a degree of polymerization of 5 to 1000.
6. The heat storage material according to claim 1 , wherein the comb polymer has a nano-phase-separated structure having nano-domains due to crystals of the crystalline side chains.
7. The amorphous main chain is a hydrocarbon-based main chain having a degree of polymerization of 5 to 1000, and the crystalline side chain is a straight or branched C 12 ~C 18 and the linking group comprises one or more groups selected from the group consisting of an amide group, a urea group, and a urethane group.
8. A heat storage film comprising the heat storage material according to any one of claims 1 to 7.
9. The heat storage film according to claim 8, wherein the average absorbance of the absorption spectrum in the wavelength range of 400 to 800 nm when formed on a glass substrate to a thickness of 100 μm is 0.5 or less.
10. A laminated heat storage film comprising the heat storage film according to claim 8 and another polymer film.